2014
DOI: 10.1038/srep05052
|View full text |Cite
|
Sign up to set email alerts
|

PCR amplification of repetitive DNA: a limitation to genome editing technologies and many other applications

Abstract: Designer transcription-activator like effectors (TALEs) is a promising technology and made it possible to edit genomes with higher specificity. Such specific engineering and gene regulation technologies are also being developed using RNA-binding proteins like PUFs and PPRs. The main feature of TALEs, PUFs and PPRs is their repetitive DNA/RNA-binding domains which have single nucleotide binding specificity. Available kits today allow researchers to assemble these repetitive domains in any combination they desir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
104
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 105 publications
(112 citation statements)
references
References 41 publications
1
104
0
Order By: Relevance
“…The formation of artefacts, or megaprimers, that lead to the laddering effect and/or the mismatch of the desired fragment, can be caused by misalignment or slippage of the polymerase when it faces secondary structures in the sequence. Several studies suggest the hypotheses and mechanisms underlying such errors (Meyerhans et al, 1990;Sahdev et al, 2007;Hommelsheim et al, 2014;Tang and Chilkoti, 2016).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The formation of artefacts, or megaprimers, that lead to the laddering effect and/or the mismatch of the desired fragment, can be caused by misalignment or slippage of the polymerase when it faces secondary structures in the sequence. Several studies suggest the hypotheses and mechanisms underlying such errors (Meyerhans et al, 1990;Sahdev et al, 2007;Hommelsheim et al, 2014;Tang and Chilkoti, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we started with the recommended method by Hommelsheim et al (2014). The authors suggested that primers that anneal far upstream or downstream of the desired sequence reduce the amount of incomplete PCR fragments.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…If a permissive promoter position has been identified a set of VarSeTALEs could be transformed into the organism of interest, rapidly producing a set of transgenic lines differing in expression of the native gene of interest. This approach would be applicable for activator or repressor dTALEs, both of which have already been used in a range of host organisms (12,35,37).…”
Section: Comparing Varsetale Design Approaches: Intra-versus Inter-rementioning
confidence: 99%